Creativity and spirituality as an inextricable tandem in the process of Italian language mastering [Креативность и духовность как неразрывный тандем в процессе усвоения итальянского языка] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Bogotá (Colombia) : Universidad Nacional de Colombia, 2015)
В данной статье креативность рассмотрена как динамически нарастающая жизнесозидающая направленность человека. Обоснована взаимосвязь духовности с креативностью. Доказано их совокупное влияние на усовершенствование процесса лингвообучения, что в совокупности активирует природный инстинкт успеха, параллельно улучшая психо-сомофизиологическое самочувствие и эффективность жизнедеятельности личности. Раскрыта структура саморазвивающейся психологической обучающей системы, развитие которой всецело зависит от типологических качеств и интеллектуально-поведенческих способностей руководителя. Подтверждена эффективность применения научно- методического подхода (как единого для изучения любого иностранного языка) и интенсивной лингвопрограммы, которые были разработаны автором: они основаны на схематизации и лаконичности учебного материала, познавательной вовлеченности и мотивации, реализации личных желаний и устремлений, позитивном эффекте удивления-неожиданности, прочном долговременном лингвостереотипе, самопроизвольной активации лингвоинтуиции, быстрой выработке навыка понимания иностранной речи и говорения на изучаемом иностранном языке.
In this article, creativity was considered as a vital, dynamic, creative, and growing orientation of the human-being. The relationship between creativity and spirituality was argued. Its accumulative impact in the perfection of the language learning process was proved, which at the same time, activates the natural instinct of success, improving simultaneously the psychophysiological wellbeing and the individual’s efficiency of the vital activity. The structure of the psychological and didactic self-developing teaching system was revealed, whose deployment depends entirely on the typological characteristics and intellectual-behavioral abilities of the head. The effectiveness of the scientific-methodical approach (being common for any foreign language studying) and intensive linguistic program, both elaborated by the author, was confirmed. They are based on the following: the schematization and laconic brevity of the teaching material, the cognitive implication and motivation, the realization of personal desires and aspirations, the positive effect of surprise and unexpectedness, a firm and durable linguistic stereotype, the spontaneous activation of the linguistic intuition, and the fast development of understanding and speaking skills in the foreign language to be studied.
Keywords: креативность как жизнесозидающая направленность; духовность; синергия; лингвоинтуиция; лингвостереотип; creative life-orientation; spirituality; psychological; synergy; linguo-intuition; linguo-stereotype